c - d (b, 2003)
Articles on economic development projects taken up in Bangladesh since 1971 and resultant changes; includes articles on politics and administration.
In Bengali.
Keywords: Economic development projects -- Bangladesh; Bangladesh -- Politics and government -- 1971-